2020
DOI: 10.14569/ijacsa.2020.0110118
|View full text |Cite
|
Sign up to set email alerts
|

Sign Language Semantic Translation System using Ontology and Deep Learning

Abstract: Translation and understanding sign language may be difficult for some. Therefore, this paper proposes a solution to this problem by providing an Arabic sign language translation system using ontology and deep learning techniques. That is to interpret user's signs to different meanings. This paper implemented ontology on the sign language domain to solve some sign language challenges. In this first version, simple static signs composed of Arabic alphabets and some Arabic words started to translate. Deep Convolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The performances of the proposed approach with existing state of-the-art techniques on the ArSL2018 dataset in terms of accuracy is shown in Table 8. The findings indicate that the proposed ArSL-CNN model when applying SMOTE resampling to the dataset is superior to two state-of-the-art methods in terms of overall accuracy [1], [3]. Ghazanfar et al [1] used CNN and achieved an accuracy of 95.9%, whereas Elsayed and Fathy [3] applied semantic DL and obtained an accuracy of 88.8%.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…The performances of the proposed approach with existing state of-the-art techniques on the ArSL2018 dataset in terms of accuracy is shown in Table 8. The findings indicate that the proposed ArSL-CNN model when applying SMOTE resampling to the dataset is superior to two state-of-the-art methods in terms of overall accuracy [1], [3]. Ghazanfar et al [1] used CNN and achieved an accuracy of 95.9%, whereas Elsayed and Fathy [3] applied semantic DL and obtained an accuracy of 88.8%.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 89%
“…Also, increasing the size of the dataset from 33406 samples to 50000 samples resulted in a further increase in the proposed model test accuracy from 94.1% to 95.9%, respectively. Elsayed and Fathy [3] examined the capacity of ontology technologies (semantic web technologies) and DL to design a multiple sign language ontology for feature extraction using CNNs for the ArSL recognition task. Their findings revealed that the recognition rates of the ArSL training and testing sets were 98.06% and 88.87%, respectively.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…With a score of 99.52%, the suggested system based on residual network ResNet101 obtained the greatest accuracy. Elsayed and Fathy [11] trained and tested Deep CNN architecture on an Arabic sign language dataset. Their experimental results show that the training set's classification accuracy was 98.6%, while the testing sets was 94.31%, according to the collected dataset.…”
Section: Related Workmentioning
confidence: 99%
“…The availability of a well-defined system model for carrying out all design tasks, including adjustments and evaluation of the system, is crucial for the system engineers and stakeholders in the acquisition of the system. The use of ontology enables system engineers to not only model metadata concepts but also semantic contexts that can be used in model inference and transformation rulemaking [6]- [8]. Ontology facilitates the process of managing the data obtained because *Corresponding Author www.ijacsa.thesai.org ontology allows the proper arrangement of the entire system [9].…”
Section: Introductionmentioning
confidence: 99%